Key role of anions in the 2D-3D electrochemical deposition of Rh on Ag electrodes - Schulz, Eduardo Nicolás (2015)
We have studied the electrochemical deposition of Rh on polycrystalline Ag substrates from electrolytes containing chloride and sulphate anions. Chronoamperometry and cyclic voltammetry have been employed in order to elucidate the growth mechanism. Anions play a key role in the growth mechanism and the resulting structures. In the presence of sulphate anions Rh deposition follows a 3D nucleation - growth mechanism, while a 2D nucleation - growth is obeyed in the case of electrolytes containing chloride anions. Ab initio thermodynamics studies support the hypothesis that chloride anions stabilize the Rh deposition favouring a 2D mechanism at low overpotentials in good agreements with the experimental data.